2021
DOI: 10.1037/adb0000737
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and cannabis co-use and social context as risk pathways to sexual assault.

Abstract: Objective: Simultaneous use of alcohol in combination with cannabis ("co-use") is common among young adults, and associated with myriad consequences. Yet no studies have examined how co-use may confer vulnerability for sexual assault (SA). Further, though both co-use and SA commonly occur in social settings, there have been no examinations of the role that co-use may play in the broader social context that leads to assault risk. This was the objective of the present study. Method: In a community sample of youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 88 publications
0
19
0
Order By: Relevance
“…Although most papers examined consequences broadly, a subset of papers investigated specific consequence types, including academic, cognitive, social, sexual, aggression, and sleep-related. 6 , 23 , 24 , 36 , 65 , 67 , 68 , 70 72 Compared to those who used alcohol only, individuals who engaged in SAM use were at higher risk across consequence types, 6 , 23 , 24 , 36 including alcohol-related harms (e.g., problems with relationships, finances, work, or health). 6 Fewer papers included individuals who used alcohol and marijuana concurrently but did not engage in SAM use, as a comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Although most papers examined consequences broadly, a subset of papers investigated specific consequence types, including academic, cognitive, social, sexual, aggression, and sleep-related. 6 , 23 , 24 , 36 , 65 , 67 , 68 , 70 72 Compared to those who used alcohol only, individuals who engaged in SAM use were at higher risk across consequence types, 6 , 23 , 24 , 36 including alcohol-related harms (e.g., problems with relationships, finances, work, or health). 6 Fewer papers included individuals who used alcohol and marijuana concurrently but did not engage in SAM use, as a comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately one third of adolescents in the United States report using both alcohol and cannabis prior to age 16 (Moss et al, 2014) and the number of young adults aged 18–22 years who use both alcohol and cannabis steadily increased from 2002 to 2018 (McCabe et al, 2021). Across adolescents and adults, individuals reporting both alcohol and cannabis use, referred to herein as “co-use,” are at greater risk of experiencing substance-related negative consequences compared to individuals who only consume alcohol and do not use cannabis (Jackson et al, 2020; Kelly et al, 2015; Read et al, 2021; Subbaraman & Kerr, 2015). Notably, cannabis use among adults who drink alcohol is associated with subsequent development and maintenance of alcohol use disorder (AUD; Blanco et al, 2016; Thompson et al, 2021; Weinberger et al, 2016).…”
mentioning
confidence: 99%
“…. Across adolescents and adults, individuals reporting both alcohol and cannabis use, referred to herein as "co-use," are at greater risk of experiencing substance-related negative consequences compared to individuals who only consume alcohol and do not use cannabis (Jackson et al, 2020;Kelly et al, 2015;Read et al, 2021;Subbaraman & Kerr, 2015). Notably, cannabis use among adults who drink alcohol is associated with subsequent development and maintenance of alcohol use disorder (AUD; Blanco et al, 2016;Thompson et al, 2021;Weinberger et al, 2016).…”
mentioning
confidence: 99%
“…Specifically, participants most often reported going out with one additional person (37%) or a small group of two-five peoples (36%) relative to medium (19%) or large (8%) groups (Read et al, 2021). When going out with one additional person, women reported that this additional person was male (71%) more often than female (29%) and a romantic partner (61%) more often than a friend (35%) or individual of another relationship (4%; Read et al, 2021). When going out with a group of people, women most often reported about even numbers of women and men in the group (60%; Read et al, 2021).…”
Section: Descriptive Statisticsmentioning
confidence: 99%